Synthesis and characterization of a new morpholine-containing sulfur ligand and transition metal complexes of Co(II), Ni(II) and Cu(I) - Görgülü, AO; Arslan, M; Çil, E (Taylor & Francis Ltd, 2005)
Potassium 1,3-dimorpholinopropan-2-O-xanthate (LK) and its complexes with Co(II), Ni(II) and Cu(I) ions have been prepared and characterized as [CoL2(H2O)(2)], [NiL2(H2O)(2)] and CuL center dot 2H(2)O by FT-IR. H-1 and (CNMR)-C-13 spectroscopies, elemental analyses, magnetic susceptibility and TGA techniques.
Keywords: Co(II); Ni(II) and Cu(I) complexes; xanthate